Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Kinerja pada Kurir Shopee Xpress Hub Cakung - Nurul Rahmah; Edward Efendi Silalahi; Hasanuddin Hasanuddin (Institut Nalanda, 2024)
This study aims to determine the effect of workload and job satisfaction on performance on the Shopee Xpress Hub Cakung Courier. The research method used is quantitative research with sampling technique that is simple random sampling and the slovin formula obtained by 148 respondents. However, data was successfully collected from 151 respondents to improve validity and reliability. Data were collected through questionnaires with (scale Likert 1-4) and analyzed using multiple linear regression tests with SPSS version 26. The results showed that the workload did not affect and insignificant to performance with a calculated t value -1,175 < 1,976 (t table) and Sig 0.242 > 0.05. Meanwhile, job satisfaction influence and significantly to performance with a calculated of t value 4.358 > 1.976 (t table) and Sig 0,000 < 0.05. Then, the calculated F value 9.547 > 3.06 (f table) and Sig 0,000 < 0.05 show that workload and job satisfaction simultaneously affect the performance on the Shopee Xpress Hub Cakung Courier. This study provides important insight into the factors that affect courier performance, with special emphasis on the importance of workload and job satisfaction in improving performance.